Biologi reproduksi ikan belanak (Moolgarda engeli, Bleeker 1858) di Pantai Mayangan, Jawa Barat [Reproduction and spawning patterns of the mullet (Moolgarda engeli, Bleeker 1858) in Mayangan Coastal Waters, West Java] - Kanti Nuti Wigati; Lenny S. Syafei (Jurnal Iktiologi Indonesia, 2013)
The aim of this research was to study reproduction and spawning patterns of the mullet (Moolgarda engeli, Bleeker 1858). This research was conducted in May-October 2011 and fish were captured by using trammel net with mesh size of 0.75; 1.5; 2.5 inch. Total fish caught during research were 226 fish comprising 146 males and 80 females. The range of total length and total weight of fish sample were 129-230 mm and 20.55-99.65 g. Sex ratios of mature fish for male and female was 1:1.4 among mature fish. Condition factors ranged from 0.38 to 1.69. The mature fish with the highest gonadosomatic index (GSI) was found in August. Total fecundity of mullet ranged from 63,627-132,106 eggs and this species was categorized as total spawner. Abstrak Penelitian ini bertujuan untuk mengkaji biologi reproduksi dan pemijahan ikan belanak (Moolgarda engeli, Bleeker 1858). Penelitian ini dilakukan pada Mei-Oktober 2011 dan ikan ditangkap dengan menggunakan alat tangkap jaring berlapis dengan ukuran mata jaring 0,75; 1,5; 2,5 inci. Total ikan contoh yang tertangkap selama penelitian berjumlah 226 ekor, terdiri atas 146 ekor ikan jantan dan 80 ekor ikan betina. Kisaran panjang total dan bobot total ikan yang tertangkap masing-masing adalah 129-230 mm dan 20,55-99,65 g. Nisbah kelamin ikan jantan dan betina yang matang gonad adalah 1:1,4. Faktor kondisi ikan belanak berkisar antara 0,38-1,69. Ikan yang matang gonad dengan IKG ter-tinggi berada pada bulan Agustus. Fekunditas total berkisar 63.627-132.106 butir dan spesies ini dikelompokkan seba-gai ikan pemijah serempak.